Modulation of DNA topoisomerase II activity and expression in melanoma cells with acquired drug resistance - Lage, Hermann; Röckmann, Heike; Schadendorf, Dirk (British journal of cancer, 2000)
The role of DNA topoisomerases (Topo) IIα and IIβ was investigated in various drug-resistant melanoma cells. Melanoma cells resistant to etoposide, exhibited an up to tenfold reduced Topo II activity corresponding to an increasing degree of drug resistance indicating that modulation of Topo II activity contribute to the drug-resistant phenotype. The reduction of Topo II activity was reflected by decreased nuclear amounts of both Topo II isoforms.
Gesehen am 22.02.2019